Frequency of Intestinal Parasites in Stool Samples - Sumaira Zareef, Humaira Zafar, Rubina Mansoor, Mobeena Ehsan , Bahram Mazhari, Umar Awaan, Abbas Hayat (Journal of Rawalpindi Medical College, 2010)
Background: To study the frequency of intestinal parasites in the stool specimens Method: In this cross sectional study, 643 samples of stool were collected. Each stool sample was analyzed grossly and microscopically. Results: The highest prevalent infections were of the protozoan (84.9%). Entamoeba histolytica(63.5%), followed by Giardia lamblia(1.4% were the most prevalent. The cases of helminthiasis (Ascaris lumbricoides, Hymenolepis nana, Ankylostoma duodenale, Enterobius vermicularis and Taenia Saginata) came out to be 14.9%. Conclusion: Protozoal infections due to Entamoeba histolytica and Giardia lamblia are much more prevalent than the helminthiasis . The prevalence of intestinal parasitic infections was higher in males (62%) than females (38%).